Law and employment : lessons from Latin America and the Caribbean - Heckman, James J. (Univ. of Chicago ChicagoUS, 2004)
Analyzes the effects of regulation and deregulation on Latin American labour markets. Presents empirically grounded studies on the costs of regulation.